2018
DOI: 10.1177/0300060518773023
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity pulsed ultrasound enhances antibiotic release of gentamicin-loaded, self-setting calcium phosphate cement

Abstract: ObjectiveThis study aimed to investigate the effect of low-intensity pulsed ultrasound on antibiotic release from gentamicin-loaded, self-setting calcium phosphate cement.MethodsA gentamicin-loaded calcium phosphate cement cylinder was eluted in stimulated body fluid. Low-intensity pulsed ultrasound (46.5 kHz, 200 mW/cm2) was used to produce a sinusoidal wave in the experimental group. Non-gentamicin calcium phosphate cement was used in the control group.ResultsThe transient concentration and cumulatively rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A peculiar work from 2018 by Shi et al [ 112 ] reported on the results obtained by influencing the release of gentamicin from a CPC by means of the use of a low-intensity pulsed ultrasound (LIPUS). Here, the authors explored conditions that are more related to the fluid dynamics rather than to the chemical characteristics of the release medium itself.…”
Section: Release Mediummentioning
confidence: 99%
“…A peculiar work from 2018 by Shi et al [ 112 ] reported on the results obtained by influencing the release of gentamicin from a CPC by means of the use of a low-intensity pulsed ultrasound (LIPUS). Here, the authors explored conditions that are more related to the fluid dynamics rather than to the chemical characteristics of the release medium itself.…”
Section: Release Mediummentioning
confidence: 99%
“…Recently, Shi et al demonstrated that sonication enhanced and prolonged the release of high concentrations of vancomycin and gentamicin from calcium phosphate cement, which serves as a basis for bone cement used to fill bone defects. [88,89] It was suggested that the improved release of antibiotics from bone cement is caused by microstreams arising from stable cavitation and US thermal effects. The USinduced antibiotic release from a bone implant is accompanied by other well-known effects of ultrasonic treatment, including the direct destruction of bacteria, an increase in antibacterial drug activity, and an increase in tissue permeability for antibiotics.…”
Section: Release Of Antibiotics From Implanted Materialsmentioning
confidence: 99%
“…Thus, US can enhance the bactericidal effect of immobilized antibiotics in two ways: by increasing their antibacterial activity and by enhancing and prolonging their release from the implants. [87][88][89] However, some adverse effects of US should be taken into account. Cavitation phenomena, which are necessary to stimulate drug release from the carrier or drug transport into cells, can be harmful to the tissues.…”
Section: Release Of Antibiotics From Implanted Materialsmentioning
confidence: 99%